Castleman's disease with isolated extensive cervical involvement - Yildirim, Hanefi; Cihangiroglu, M.; Ozdemir, H.; Kabaalioglu, A.; Yekeler, H.; Kalender, O. (My University, 2005)
Castleman's disease is a lymphoproliferative disorder of uncertain cause characterized by a distinctive pattern of hypervascular lymphoid hyperplasia. Computed tomography and MRI can be used to define the extent of disease. The latter may be used to detect curvilinear hypointensities within the abnormal node. Symmetrical involvement of nasopharyngeal and parapharyngeal regions in our case without disease elsewhere is considered to be an unusual presentation.
Keywords: Castleman's disease; Computed tomography; Magnetic resonance imaging; Neck; Sonography